(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
This article describes the role and importance of future history teachers in the development of knowledge of modern concepts of the philosophy of history. Also, the opinions of the authors on the development of knowledge of modern concepts of the philosophy of history among future history teachers were analyzed.